Science in Dagestan. The 1960s: history, problems - Mirzabek Yahyaevich Mirzabekov (Вестник Майкопского государственного технологического университета)
The article shows the development of academic and university science in the region in the 60s of the twentieth century with the involvement of diverse factual materials. Positive changes in the spectrum of scientific research directions in the institutes and departments of the Dagestan branch of the USSR Academy of Sciences, universities of the republic have been traced. Favorable results have been noted in improving the human resources potential in the postgraduate course of the Dagestan branch of the USSR Academy of Sciences and universities of the republic. The author has come to a reasonable conclusion that the studied decade was characterized by a further expansion of the network of scientific institutions, an increase in the number of researchers in academic and branch research institutes, higher educational institutions of the republic and an increase in the development of topical scientific problems of natural science and humanities profiles in them. Representatives of Dagestan nationalities made up the main contingent of researchers and teachers of universities of the republic in the new conditions. At the same time, despite the increase in the number of female scien- tists, including Dagestanis, men continued to prevail in them.